Selected Filipino-Chinese small-medium entrepreneur communication management practices in the Philippines - Ditan, Carolina D. (Faculty of Communications Science, Dr. Soetomo University, 2022)
Chinese entrepreneurial activities diaspora in Southeast Asia have received ample attention in academic debates. This academic attention is related to an impressive business presence of ethnic Chinese companies in the region, which seek explanations. Several works of literature have emerged arguing that because of specific cultural traits (personal networks, ethnic affinity, and Confucian Work Ethics), ethnic Chinese businesses function successfully in their new home countries and business contacts across borders. This study aims to describe the communication management practices of Filipino-Chinese Small Medium Enterprises (SME) entrepreneurs in terms of planning, leadership, organising and control. The method used in this study is phenomenology with data collection using interviews with six respondents and three Philippine government officials. The conclusion of this study shows that in terms of risk behaviour, the Filipino-Chinese entrepreneurs had a positive outlook by believing that taking risks is one key factor in business success.